Sodomites in the pillory in eighteenth-century London - Bartlett, Peter (Sage, 1997)
The arrival of the eighteenth century brought with it new legal attention to sodomitical behaviour. Nowhere was this more notorious and public than in the punishment of those offences in the pillory. This paper argues that the pillory was a productive space for the understanding of sodomy in this period, a place where the logic and practice of that particular punishment intersected with a new and emerging conceptualization of masculinity and erotic desire between men. The intersection between these discourses had a dynamic function: far from merely reflecting public attitudes prevalent elsewhere, the practices of the pillory helped to create the new attitudinal structure to sodomitical behaviour.